Effect of Risperidone and Fluoxetine on the Movement and Neurochemical Changes of Zebrafish - Prieto, María Jimena (2012)
Brain developmental disorders in humans, including Autism Spectrum Disorders (ASD) and Down’s syndrome, have been linked to increased serotonin levels. This work was designed to study changes in serotonin levels in the early stages of development with two classes of antipsychotic drugs: Risperidone, a drug that blocks serotonin and dopamine receptors, and fluoxetine, a serotonin reuptake inhibitor. The use of antipsychotic drugs is a solid choice to study the decrease and increase of these neurotransmitters and their influence on development. The study of these parameters will give an idea of the effects of serotonin in early developmental stages. To this end, we examined the effects of risperidone and fluoxetine on the locomotor activity, heart rate and brain development of zebrafish larvae. Our results showed that in larvae exposed to fluoxetine alone, swimming was significantly increased at 9 dpf (days post-fertilization). Erratic and abnormal movements were observed suggesting a toxic effect of fluoxetine. No erratic swimming was observed in larvae treated with fluoxetine plus risperidone. Both drugs presented morphological changes in dopaminergic neurons and mononeurons. Exposure to fluoxetine plus risperidone indicated possible reversal effects. Studies in zebrafish allow obtaining new insights into the side effects of these drugs as well as into the brain control of locomotor activity. Testing several drug-induced changes in behavior and serotonin levels is one of the experimental approaches for screening a new therapeutically relevant compound, and thus, merits further research.